2008
DOI: 10.1136/ard.2008.096743
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumour necrosis factor and IL-17 production by leflunomide involves the JAK/STAT pathway

Abstract: Objective:To study the effects of different disease-modifying antirheumatic drugs (DMARD) on different events mediated by IL-15-activated lymphocytes.Methods:Peripheral blood lymphocytes (PBL) were isolated from healthy donors and activated with IL-15 after exposure to different DMARD: leflunomide, cyclosporin A, methotrexate, mycophenolic acid, FK-506, sulphasalazine and sodium aurothiomalate. The expression of different surface molecules on the PBL was then determined by flow cytometry. Cells were also co-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…In that study, both TNF-a and IL-17 were inhibited by leflunomide. 28 However, we found specific inhibition of IL-17 by 4SC-101 when cells were stimulated with PHA. The different TNF-a inhibition results described here could be due to the involvement of specific intracellular signaling pathways (JAK/STAT or NF-jB, respectively) in these two studies when utilizing either IL-15 or PHA stimulation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In that study, both TNF-a and IL-17 were inhibited by leflunomide. 28 However, we found specific inhibition of IL-17 by 4SC-101 when cells were stimulated with PHA. The different TNF-a inhibition results described here could be due to the involvement of specific intracellular signaling pathways (JAK/STAT or NF-jB, respectively) in these two studies when utilizing either IL-15 or PHA stimulation.…”
Section: Discussionmentioning
confidence: 93%
“…24,25 Recently, IL-17 has also gained increasing attention as a key mediator in the pathogenesis of intestinal inflammation. 11,17,18,[26][27][28] Of some relevance, leflunomide can inhibit IL-15 induced cytokine production by lymphocytes. 28 Our results (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in depletion of intracellular pyrimidines which can be reversed by addition of uridine. However, it has also been reported that A771726 can inhibit the JAK/STAT pathway induced by cytokines (31,32,55). Accordingly in our hands, this compound induced uridine-reversible inhibition of CD40L/IL-4-stimulated CLL proliferation at low levels (3-5mg/mL) without interfering with STAT phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments in murine cell lines have shown that teriflunomide inhibits protein tyrosine-kinase (PTK) activity via inhibition of interleukin 2(IL-2)-induced tyrosine phosphorylation. [36][37][38] Specifically, teriflunomide inhibits the janus tyrosine kinases jak1 and jak3 in an IL-2 dependent murine cytotoxic T cell line. Several effects result from the inhibition of PTK activity including reduced T-cell proliferation, reduced production of IL-2, inhibition of calcium mobilization, and a blockage of immunoglobulin G1 production.…”
Section: Inhibition Of Protein Tyrosine Kinasesmentioning
confidence: 99%